Applying Analytical Hierarchy Process to Evaluate Adult Occupant Protection on Body Region in ASEAN NCAP Offset Frontal Test Domain - Hanida, Abdul Aziz; Ezrin Hani, Sukadarin; Nurud Suria, Suhaimi; Hairunnisa, Osman; Mimi Nabila, Mohd Nordin; Ikram, Shafie (Society of Automotive Engineers Malaysia, 2018)
Adult Occupant Protection (AOP) is a vital area of evaluation in all New Car Assessment Programs (NCAPs) around the globe. The primary objective of these new car assessment programs is to reduce road deaths by focusing on vehicle (pre-crash) safety features. Starting from the year 2017 until 2020, a single rating system has been introduced whereby AOP contributes 50% to the overall rating with a maximum of 36 points; split into three main domains including offset frontal test (OFT), side impact test (SIT) and head protection technology (HPT). However, the extent of OFT protection to car drivers and passengers during a collision still needs to be explored. Therefore, in this study, an evaluation of body region injury due to AOP failure in frontal crash is conducted to validate and support NCAP rating. Analytic hierarchy process (AHP) is put forward on the basis of expert’s input from various related fields to evaluate the injury to body regions and OFT protection during an accident based on the current situation. The results show that head, neck and chest indicated the highest severity, followed by knee, femur and lower leg with respect to the Consistency Ratio (CR) of 0.0633. This was in line with the focus of ASEAN NCAP’s AOP protocol whereby the three body regions were deemed as the critical parts and required sufficient protection. Based on the findings, it is proven that ASEAN NCAP’s consideration of OFT in AOP is well developed and suits the current needs.